2019
DOI: 10.1002/fsn3.1351
|View full text |Cite
|
Sign up to set email alerts
|

Possible use of organic compounds on shelf life and quality properties of peeled pomegranate

Abstract: Pomegranate cultivar ("Ardestani") peeled and packed in polyethylene containers and treated with different natural products. Two concentrations of Aloe vera gel (10 and 15%), two different levels of saffron petal extracts (10 and 20% V/V) and two concentrations of saffron style extract (0.1 and 1% V/V) and control in one storage condition (7°C and 85% RH) were the treatments that applied by a full factorial randomized method. We examined natural substances for their possible application in extending the shelf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…These parameters increased with AV content with values of 216 ± 2 • C and 223 ± 6 • C for FG, 221 ± 1 • C and 230 ± 2 • C for FG/AV1 and 228 ± 1 • C and 237 ± 4 • C for FG/AV4, respectively. This behaviour was associated with the antioxidant effect induced by the presence of bioactive compounds, such as polyphenols, quinones and polysaccharides, in AV, in agreement with the TPC and antioxidant activity results obtained in this work [11,12,19,21]. Some authors have also reported a slight increase in the degradation temperature of alginate-based blends with the addition of Aloe Vera due to the formation of polymer-polymer interactions [20].…”
supporting
confidence: 89%
See 1 more Smart Citation
“…These parameters increased with AV content with values of 216 ± 2 • C and 223 ± 6 • C for FG, 221 ± 1 • C and 230 ± 2 • C for FG/AV1 and 228 ± 1 • C and 237 ± 4 • C for FG/AV4, respectively. This behaviour was associated with the antioxidant effect induced by the presence of bioactive compounds, such as polyphenols, quinones and polysaccharides, in AV, in agreement with the TPC and antioxidant activity results obtained in this work [11,12,19,21]. Some authors have also reported a slight increase in the degradation temperature of alginate-based blends with the addition of Aloe Vera due to the formation of polymer-polymer interactions [20].…”
supporting
confidence: 89%
“…Within the wide range of substances used as active additives, natural products obtained from plants are gaining attention because of consumers’ rejection to antioxidants from synthetic origin based on potential toxicity and possible carcinogenic effects [ 10 ]. In the last decade, the antioxidant, antimicrobial, antidiabetic, hepatoprotective, anticarcinogenic and antihyperlipidemic effects of Aloe Vera (AV) gel extract have been extensively proved for food packaging applications [ 11 , 12 , 13 ]. These properties are a consequence of the high content on unique polysaccharides (e.g., glucomannan, acemannan), phenolic compounds (flavonoids and anthraquinones), organic acids and vitamins (B 1 , B 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[8,10] Aloe vera, due to the presence of some bioactive components having antioxidant properties, has been used in edible films for enhancing the storage life of various vegetables and fruits. [11][12][13] Aloe vera gel possess vitamins, bioactive polysaccharide, and phenolic compounds. [14] Researchers agree that the observed beneficial effects of the aloe vera may be because of the synergistic effect of the 75 bioactive components.…”
Section: Introductionmentioning
confidence: 99%